Indexing of Voluminous Data Using K-D Tree with Reference to CBIR - Das, Jayashree; Gogoi, Minakshi (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes a fast and efficient indexing technique that can be used in an image indexing and retrieval system for voluminous image data. The proposed technique is based on K-d tree which uses multi-dimensional features. At first the colour feature of a set of images are extracted. Then an index tree is generated with K-d tree index based on these colour features. After indexing is done the efficiency of the method is tested against search time for the collected dataset. The validation of the method is also tested with and without indices for the said dataset.